Pengaruh variasi kecepatan udara dan massa bahan terhadap waktu pengeringan jagung pada alat fluidized bed - Syahrul, S.; Romdhani, R.; Mirmanto, Mirmanto (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2016)
Indonesia is an agricultural country that has many agricultural products so that post-harvest handling is necessary so that the crop is not quickly broken when stored or distributed. One harvests in Indonesia, which require post-harvest handling such as corn. Based on SNI, the maximum moisture content of corn feed raw material has a moisture content of 14%. The water content of the corn used is 20% with a tolerance of ± 0.5%. Variations air speed used is 5 m /s, 6 m /s and 7 m /s with a variation of the mass of material that is 0.5 kg, 1 kg, and 1.5 kg. With the variation of air velocity and mass of the material showed that the higher the speed of the air, the faster drying time. In addition, the heavier material is drained, it will take longer. Variations of air velocity and mass of materials that require the fastest drying time is the air speed of 7 m /s with a mass of 0.5 kg. Variations of air velocity and mass of material that takes the longest drying air is at a speed of 5 m / s with a mass of 1.5 kg of material.